2019
DOI: 10.14715/cmb/2019.65.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morning and nocturnal soccer matches on levels of some trace elements in young trained males

Abstract: The aim of this study was to comparatively evaluate effect of morning and nocturnal soccer matches induced metabolic stress on plasma levels of iron (Fe), copper (Cu) and zinc (Zn). Twenty male footballers performed two soccer matches in morning and at night on different days. Blood samples were taken before and after match. The levels of Fe, Zn and Cu were measured through an atomic absorption spectrophotometry. Metabolic stress was evaluated by altered malondialdehyde (MDA) levels that measured using High Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, Metin et al [ 24 ] reported no differences in plasma Zn concentrations between groups, similar to those reported by the previous authors. No differences were observed either when comparing the time of match play in plasma Zn concentrations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Metin et al [ 24 ] reported no differences in plasma Zn concentrations between groups, similar to those reported by the previous authors. No differences were observed either when comparing the time of match play in plasma Zn concentrations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been observed that serum Mo and Zn concentrations differ among sports modalities and training levels [ 21 , 22 ], as well as erythrocyte concentrations [ 7 ]. In soccer players, Algul et al [ 23 ] reported that plasma Zn concentrations decreased at the end of a match, whether the game was played in the morning or in the evening. Metin et al [ 24 ] observed no differences in Zn concentrations between male and sedentary soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…In soccer players, research is more scarce. In relation to the above, previous authors reported increases with respect to basal values in Cu concentrations after the end of a soccer match regardless of the time of the match (morning or evening) [ 24 ]. However, Metin et al [ 25 ] reported that soccer players presented lower plasma Cu concentrations in relation to the control group, being in the same line as that reported by Toro-Román et al [ 20 ].…”
Section: Introductionmentioning
confidence: 91%
“…It is generally accepted that physical activity is a valuable tool in the preventative and treatment strategy for many cardiorespiratory and metabolic diseases and other chronic diseases (Ozcelik et al, 2015& Sietsema et al, 2020. In addition to many beneficial effects of exercise on improvement of body composition, increased fat oxidation, insulin homeostasis, exercise has significant impacts on increased metabolic stress, impairment of oxidant antioxidant status and disarranged of levels of some trace elements (Algul et al, 2019). Zinc (Zn) is one of the important trace elements that have significant roles in energy metabolism and antioxidant effects (Gulbahce et al, 2021& Ugurlu et al, 2022.…”
Section: Introductionmentioning
confidence: 99%